Handbook of Research on Smart Computing for Renewable Energy and Agro-Engineering (Engineering Science Reference, 2019)
"This book examines the benefits and barriers of implementing computational models to agricultural production and energy sources as well as how these models can produce more cost-effective and sustainable solutions"--